Meningkatkan Repurchase Intention Melalui Brand Trust dan Perceived Behavioral Control Dengan Attitude Towards Halal Product Sebagai Variabel Mediasi - Chairunisa, Salsabila; Damarwulan, Liza Mumtazah; Lutfi, Lutfi (Advances In Social Humanities Research, 2025)
The halal beauty industry has experienced significant growth, but the Avoskin brand halal skincare still faces significant fluctuations in the sales of its products. Therefore, the right strategy is needed to increase repurchase intention. It is important for Avoskin as a skincare brand to identify the factors that affect repurchase intention. This study aims to analyze the influence of Brand Trust, Perceived Behavioral Control, Attitude towards Halal Product on Repurchase Intention in Avoskin brand halal skincare. This study used 207 respondents who were Avoskin consumers and the data was analyzed using the Structural Equation Modelling (SEM) method with SmartPLS 4.0.9.9 software. The results of this study show that Brand Trust and Perceived Behavioral Control have a positive and significant effect on Attitude towards Halal Product. In addition, Perceived Behavioral Control and Attitude towards Halal Product have also been proven to have a positive and significant effect on Repurchase Intention. Meanwhile, Brand Trust did not show a significant influence on Repurchase Intention. In the mediation variable, Attitude towards Halal Product has a positive and significant effect in mediating Brand Trust and Perceived Behavioral Control on Repurchase Intention.